2017
DOI: 10.4238/gmr16019022
|View full text |Cite
|
Sign up to set email alerts
|

Expression of prion protein in the cerebrospinal fluid of patients with Parkinson’s disease complicated with rapid eye movement sleep behavior disorder

Abstract: ABSTRACT. Parkinson's disease (PD) is one of the most common neurodegenerative diseases and mainly manifests with decreasing numbers of dopaminergic neurons. Rapid eye movement (REM) sleep behavior disorder (RBD) has an incidence of 15-47% in all PD patients. Prion proteins (PrPs), which are expressed in both neurons and glial cells of the brain, are believed to be correlated with abnormal neurological functions, although their role in PD-related sleeping disorders remains unclear. We therefore investigated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…In this study, we detected significant increase in CSF levels of alpha-synuclein in PD-RBD patients. Although a previous cross-sectional study in PD patients have revealed no association between CSF alpha-synuclein levels and RBD ( 46 ), prior investigations have revealed that CSF Prion Proteins (PrPs) are significantly elevated in PD patients with RBD compared to PD patients without sleep disorders ( 47 ), which might be suggestive of accelerated neuronal degeneration in PD-RBD patients and thus, introduce RBD as potentially the most appropriate clinical predictive marker of neuronal degeneration and disease progression in PD, as shown previously ( 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we detected significant increase in CSF levels of alpha-synuclein in PD-RBD patients. Although a previous cross-sectional study in PD patients have revealed no association between CSF alpha-synuclein levels and RBD ( 46 ), prior investigations have revealed that CSF Prion Proteins (PrPs) are significantly elevated in PD patients with RBD compared to PD patients without sleep disorders ( 47 ), which might be suggestive of accelerated neuronal degeneration in PD-RBD patients and thus, introduce RBD as potentially the most appropriate clinical predictive marker of neuronal degeneration and disease progression in PD, as shown previously ( 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…A longitudinal study illustrated that lower baseline amyloid-β 42 levels were predictive of cognitive decline at three-year follow-up only in PD patients with RBD [92]. Increased CSF prion protein levels have also been reported in PD patients with RBD compared to PD patients without RBD [93]. CSF inflammatory markers, including interleukin 1β and nitric oxide, as well as serum prostaglandin E2 have also been shown to be elevated in PD patients with RBD [90].…”
Section: Fluid Biomarkersmentioning
confidence: 99%
“…Anderson et al, ( 121 ) found normal hypocretin levels in the CSF of RBD subjects. Elevated expression of prion protein (PrP, both mRNA and protein) in PD patients with RBD, compared to PD patients without sleep problems and healthy controls has been recently reported ( 122 ). Although total alpha-synuclein was reportedly lower in early untreated PD patients compared to healthy controls and CSF total tau was slightly higher, the rates of changes were not significant after 24 months of follow-up and, moreover, these CSF parameters were not studied in iRBD subjects specifically so far ( 123 ).…”
Section: Diagnostic Accuracy Of Clinical Measures For Predicting Convmentioning
confidence: 99%